2018
DOI: 10.1038/s41598-018-34127-x
|View full text |Cite|
|
Sign up to set email alerts
|

Bacterial and fungal gut communities of Agrilus mali at different developmental stages and fed different diets

Abstract: Agrilus mali (Coleoptera: Buprestidae) is an invasive wood borer pest that has caused considerable damage to the Xinjiang wild fruit forest. In this study, we investigated the bacterial and fungal intestinal microbial communities of A. mali during different developmental stages, including larvae, pupae and newly eclosed adults or fed different diets (leaves of Malus halliana and Malus pumila) using Illumina MiSeq high-throughput sequencing technology. The results showed that microbial alpha diversity first inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 61 publications
4
46
4
Order By: Relevance
“…It was suggested that C. pomonella could obtain the nutrients necessary for their own growth and development by feeding different host plants in the complex environment. The high gut microbial diversity observed in shoot‐feeding G. molesta may have resulted from the vast microbiota via a specific nutritional complementation from an imbalanced diet …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It was suggested that C. pomonella could obtain the nutrients necessary for their own growth and development by feeding different host plants in the complex environment. The high gut microbial diversity observed in shoot‐feeding G. molesta may have resulted from the vast microbiota via a specific nutritional complementation from an imbalanced diet …”
Section: Discussionsupporting
confidence: 85%
“…The high gut microbial diversity wileyonlinelibrary.com/journal/ps observed in shoot-feeding G. molesta may have resulted from the vast microbiota via a specific nutritional complementation from an imbalanced diet. 47,48 At the phylum level, there were no dramatic differences in the bacterial composition of the fruit-boring lepidopteran pests. Four bacterial phyla, including Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes, were predominant (relative abundance >1%).…”
Section: Discussionmentioning
confidence: 99%
“…Sordariomycetes fungi might assist in detoxification, as many members from this fungal group were found to be involved in organic matter decomposition and known as endophytes of plants (Santana et al ., ; Zhang et al ., ). The high abundance of Sordariomycetes were also reported in the apple buprestid Agrilus mali and Asian longhorned beetle Anoplophora glabripennis across developmental stages (Zhang et al ., ; Mason et al ., ). At the genus level, a total of 278 genera of bacteria and 80 genera of fungi were annotated in all BPH samples, including culturable and unculturable bacteria and fungi.…”
Section: Discussionmentioning
confidence: 97%
“…Remarkably, there are a large number of fungal genera not previously detected in BPH, mainly including Wallemia , Talaromyces , Cladosporium , Papiliotrema , Mucor and Penicillium . Three of them ( Wallemia , Cladosporium and Penicillium ) have also previously been identified in the apple buprestid and parasitic Dendroctonus bark beetles (Dohet et al ., ; Zhang et al ., ). Future research should focus on the prevalence and possible functions of these fungal associates of BPH.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation